Rituximab induces phenotypical and functional changes of NK cells in a non-malignant experimental setting - Merkt, Wolfgang; Lorenz, Hanns-Martin; Watzl, Carsten (Arthritis Research & Therapy, 2016)
Rituximab has broad and increasing application in rheumatic diseases. It is known from lymphoma studies that natural killer (NK) cells can lyse rituximab-coated transformed B cells. However, the role of NK cells in mediating rituximab-induced depletion of non-malignant B cells is unknown. The purpose of this study was to provide fundamental data on rituximab-mediated effects on NK cells in PBMCs without tumor cells, in order to simulate effects that could be relevant in patients with rheumatic disease.
Gesehen am 21.12.2017